Talent wants to be free : why we should learn to love leaks, raids, and free riding - Lobel, Orly (Yale University Press, 2013)
This timely book challenges conventional business wisdom about competition, secrecy, motivation, and creativity. Orly Lobel, an internationally acclaimed expert in the law and economics of human capital, warns that a set of counterproductive mentalities are stifling innovation in many regions and companies. Lobel asks how innovators, entrepreneurs, research teams, and every one of us who experiences the occasional spark of creativity can triumph in today's innovation ecosystems. In every industry and every market, battles to recruit, retain, train, energize, and motivate the best people are fierce. From Facebook to Google, Coca-Cola to Intel, JetBlue to Mattel, Lobel uncovers specific factors that produce winners or losers in the talent wars. Combining original behavioral experiments with sharp observations of contemporary battles over ideas, secrets, and skill, Lobel identifies motivation, relationships, and mobility as the most important ingredients for successful innovation. Yet many companies embrace a control mentality--relying more on patents, copyright, branding, espionage, and aggressive restrictions of their own talent and secrets than on creative energies that are waiting to be unleashed. Lobel presents a set of positive changes in corporate strategies, industry norms, regional policies, and national laws that will incentivize talent flow, creativity, and growth. This vital and exciting reading reveals why everyone wins when talent is set free.